Public Values in the Age of Big Data: A Public Information Perspective. Issue 2 (4th December 2018) - Ingrams, Alex
Abstract : Public administration scholars have so far largely viewed big data as a kind of technocratic transformation. However, through citizens' digital records, use of service apps, social media, digital sensors, and other digital footprints, big data also gives policymakers insights into citizen choices and is therefore potentially supportive of public values such as participation and openness. Focusing on two underexplored countries, Germany and the Netherlands, this article develops a public values framework for big data that considers citizen values alongside technocratic ones. It takes the particular case of public information agencies such as ombudsmen and courts of audit, examining the functions they play and whether they have the capacity to address tensions arising between technocratic and citizen values. The study finds that, while capacity does exist, it is heavily tilted toward technocratic values, with no capacity to address participative values. Finally, five propositions are advanced, which describe where the tensions lie and therefore where the attention of public information agencies should best be focused. 摘要: 公 共行政学者至今已在很大程度上将大数据视为一种技术官僚转变(technocratic transformation)。然而, 通过获取公民的数据记录、服务性应用程序的使用、社交媒体、数字传感器、以及其他数据足迹, 大数据同时还能给政策制定者提供关于公民选择的见解, 并因此以一种潜在的方式支持公共价值观, 例如参与和开放。通过聚焦于德国和荷兰这两个尚未被充分探究的国家, 本文就大数据提出了一项公共价值观框架, 该框架考量了公民价值观和技术官僚价值观。框架将例如政府巡查机关和审计院这类公共信息机构作为特别案例, 检验其充当的作用, 和其是否有能力解决技术官僚价值观和公民价值观之间的紧张关系。研究发现, 尽管此类机构存在相关能力, 但这种能力严重倾向技术官僚价值观, 无法应对(公民)参与价值观。最后, 本文提出了五项提议, 用于描述紧张关系的源头, 公共信息机构因此能将关注点有效聚焦于这一紧张关系。 Resumen: Los académicos de la administración pública han hasta ahora percibido al Big Data como un tipo de transformación tecnocrática. Sin embargo, a través de los registros digitales de los ciudadanos, el uso de aplicaciones de servicios, redes sociales, sensores digitales y otras huellas digitales, Big Data también les brinda a los políticos ideas sobre las elecciones de los ciudadanos y, por lo tanto, puede apoyar valores públicos como la participación y la apertura. Al enfocarse en dos países inexplorados, Alemania y Países Bajos, este artículo desarrolla un marco teórico de valores públicos para Big Data que considera los valores de los ciudadanos junto con los tecnocráticos. Toma el caso particular de las agencias de información pública, como los ombudsmen y los tribunales de auditoría, que examinan las funciones que desempeñan y si tienen la capacidad de abordar las tensiones que surgen entre los valores tecnocráticos y los de los ciudadanos. La investigación encuentra que, si bien la capacidad existe, está muy inclinada hacia los valores tecnocráticos, sin capacidad para abordar los valores participativos. Finalmente se hacen 5 propuestas que describen dónde están las tensiones, y por ende dónde debería estar la atención de las agencias de información pública.